Research protocol for a systematic review and meta-analysis of the effects of music on anxiety and physiological outcomes in patients undergoing bronchoscopy. - Amani Kacem; Dhekra Chebil; Sana Aissa; Anis Maatallah; Ahmed Abdelghani (PLoS ONE)
Introduction Bronchoscopy is a routine clinical examination that can cause discomfort and anxiety in patients. This paper presents a protocol for a systematic review and meta-analysis aiming to assess the effect of music on anxiety and physiological outcomes in patients undergoing bronchoscopy. Methods The protocol adhere to Preferred Reporting Items for Systematic Reviews and Meta-Analyses Protocols guidelines and has been registered in PROSPERO (CRD42024567398). Our documentary research strategy will involve four databases: PubMed, Google Scholar, Scopus, and the Cochrane Library. In addition, manual searches will be conducted through related articles and references. We will include randomized controlled trials that evaluate the effect of music on patients undergoing bronchoscopy. The primary outcome will be the anxiety level and the secondary outcome will include physiological outcomes. Study selection, data extraction, and quality assessment will be carried out independently by two reviewers. Any discrepancies will be resolved through consultation with a third reviewer. The quality and the risk of bias in the studies will be evaluated using The Joanna Briggs Institute critical appraisal tool. The results of this systematic review will be synthesized to provide an overview on the effectiveness of music on anxiety and physiological parameters in patients during bronchoscopy. If the results are considered acceptable and sufficiently homogeneous, a meta-analysis will be performed to synthesize the findings. Conclusion The systematic review produced from this protocol will provide evidence on the effectiveness of music for patients undergoing bronchoscopy and will contribute to strengthening the existing body of knowledge on non-pharmacological interventions for anxiety management during medical procedures.